2009
DOI: 10.2165/0003088-200948010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Analysis of Lanreotide Autogel® in Healthy Subjects

Abstract: Abstractneuroendocrine tumours. The objective of this study was to develop a pharmacokinetic model for the sustainedrelease formulation lanreotide Autogel ® after deep subcutaneous administration in healthy subjects, and to explore the potential effect of covariates, especially sex and dose. Subjects and methods:This was an open-label, single-centre, randomized, dose-ranging, parallel-group study, with a follow-up period of 4-7 months following drug administration in healthy subjects. Healthy Caucasian subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…In vivo release of lanreotide is governed by the intrinsic properties of self-assembly of the peptide itself and is most likely mediated by passive diffusion of lanreotide from the depot into the surrounding tissues, followed by the absorption to the bloodstream (Fig. 2a) [6, 29]. Indeed, PK studies confirmed the favorable PK profile expected based on the previous data.…”
Section: Lanreotide Depot Formulationsupporting
confidence: 61%
“…In vivo release of lanreotide is governed by the intrinsic properties of self-assembly of the peptide itself and is most likely mediated by passive diffusion of lanreotide from the depot into the surrounding tissues, followed by the absorption to the bloodstream (Fig. 2a) [6, 29]. Indeed, PK studies confirmed the favorable PK profile expected based on the previous data.…”
Section: Lanreotide Depot Formulationsupporting
confidence: 61%
“…The procedure was repeated 500 times, and the 2.5th, 50th, and 97.5th percentiles of the controlled values were calculated from 500 simulations.Because a simulated‐based pharmacokinetic rationale for the feasibility of extending the dosing interval for lanreotide Autogel 120 mg to 56 days has been published, 3 the percentages of control of GH, IGF‐1, and GH + IGF‐1 were also calculated after 4 consecutive injections of lanreotide Autogel 120 mg every 56 days, using the simulation procedure described above. Values of C P were simulated using the population pharmacokinetic model for LA developed in healthy volunteers, which was externally validated with data from patients with acromegaly 3 . Model and parameters used to simulate C P are presented in supplementary material (Suppl.…”
Section: Methodsmentioning
confidence: 99%
“…The SSA lanreotide is currently available as an extended‐release formulation, lanreotide Autogel (LA) (marketed as Somatuline Depot in the United States), administered every 4 weeks (every 28 days). Recent pharmacokinetic data suggest the possibility of expanding such an interval up to 2 months (every 56 days) with the 120‐mg formulation 3 . There is considerable and recent published information supporting that LA is efficacious in controlling GH levels and/or normalizing IGF‐1 (IGF‐1 levels in the age‐adjusted range) in patients with acromegaly under different clinical scenarios 4 7 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Minimum and maximum concentrations and area under the curve followed expected dose proportionality. Based on population pharmacokinetics, and software-assisted modeling of drug disposition, minimum effective levels of lanreotide were found with a dose of 120 mg 56 days after injection 27,32. With this information, the possibility of extending the interval between injections was suggested.…”
Section: Drug Profilementioning
confidence: 99%